2008
DOI: 10.1007/s00423-007-0258-2
|View full text |Cite
|
Sign up to set email alerts
|

Validity of observation interval for synchronous hepatic metastases of colorectal cancer: changes in hepatic and extrahepatic metastatic foci

Abstract: Reevaluation after an observation interval allows accurate understanding of the number and location of hepatic metastases and is beneficial in determining candidates for surgery and in selecting treatment plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In all, 207 patients did not fulfill the selection criteria for resection: recurrence at the primary site ( n = 11), extrahepatic or extrathoracic metastases ( n = 85), unresectable liver lesions ( n = 81), unresectable lung lesions ( n = 30). When metastasis to the liver and/or lung was detected at the time of diagnosis of colorectal cancer, we resected the primary tumor first and, in the absence of disease progression, performed the metastasectomy 3 months later [21]. When patients presented with simultaneous liver and lung metastases, we resected the hepatic lesion(s) first to rule out extrahepatic abdominal lesions.…”
Section: Methodsmentioning
confidence: 99%
“…In all, 207 patients did not fulfill the selection criteria for resection: recurrence at the primary site ( n = 11), extrahepatic or extrathoracic metastases ( n = 85), unresectable liver lesions ( n = 81), unresectable lung lesions ( n = 30). When metastasis to the liver and/or lung was detected at the time of diagnosis of colorectal cancer, we resected the primary tumor first and, in the absence of disease progression, performed the metastasectomy 3 months later [21]. When patients presented with simultaneous liver and lung metastases, we resected the hepatic lesion(s) first to rule out extrahepatic abdominal lesions.…”
Section: Methodsmentioning
confidence: 99%
“…In the early 2000s, some authors proposed to adopt a time-test before surgery in patients with resectable colorectal liver metastases ( i.e. an observation period to evaluate the tumor evolution)[ 39 - 41 ]. One-third to half of the patients developed additional lesions during the time-test and were excluded from resection.…”
Section: Moving Toward a Dynamic Viewmentioning
confidence: 99%
“…The traditional approach to synchronous rectal cancer liver metastases has been a staged operation where proctectomy is performed followed by hepatectomy. The benefit of this approach is that it allows for the full metastatic load and biological aggressiveness of the tumor to be identified before the morbidity associated with hepatectomy is encountered [ 87 , 88 , 89 , 90 ]. Traditionally thought to avoid the increased morbidity and mortality from the combination of the two major operations, several studies demonstrated no increased morbidity or mortality when proctectomy is combined with partial hepatectomy [ 91 , 92 , 93 ].…”
Section: Distant Solid Organ Metastasis and Peritoneal Carcinomatosis...mentioning
confidence: 99%